KOMUNIKASI SOSIAL DALAM MENSOSIALISASIKAN PENETAPAN KEBIJAKAN GUBERNUR BALI TENTANG PEMBATASAN TIMBULAN SAMPAH PLASTIK SEKALI PAKAI - Putri, Niluh Wiwik Eka (Jurnal Nomosleca, 2019)
Abstract Bali is a tourist destination so cleanliness and the beauty of tourist areas are an absolute requirement in the world of tourism. The provincial government of Bali issued a governor regulation number 97 of 2018 concerning restrictions on the generation of disposable plastic waste. Handling waste problems is not only the responsibility of one party, but must involve all elements, namely; community, government and private sector. The existence of community-based waste management groups, as well as other stakeholders is expected to be the driver of achieving Trash-Free Indonesia in 2020, especially Bali. This study aims to determine social communication in socializing the policy of limiting the generation of plastic waste in Bali. This study uses a qualitative approach with action research methods. The results of the study show that social communication about the policy of limiting the generation of disposable plastic waste issued by the Governor of Bali has succeeded in increasing public awareness in reducing the use of plastic. In carrying out social communication, the Governor of Bali conducts social contacts in primary (direct) or secondary (mass media). With the existence of social contacts, social change occurs in accordance with what is expected by the provincial government of Bali. Keywords: Social Communication, Socialization, Governor of Bali Policy DOI :Â https://doi.org/10.26905/nomosleca.v5i1.2783